How to upgrade an enterprise’s low-carbon technologies under a carbon tax: The trade-off between tax and upgrade fee - He, Senyu; Yin, Jianhua; Zhang, Bin; Wang, Zhaohua (Applied energy, 2018)
•Proposed a new method to balance carbon tax and technology upgrade cost.•Optimised the enterprise's technology upgrade strategy under carbon tax.•Tax rate is more sensitive to enterprise with a stricter control on expected cost.•Low tax rate hardly promotes enterprise with a loose control to reduce emission.•Excessive carbon tax makes enterprise give up its technology upgrade plan. Reducing CO2 emissions is a hot topic, and an important policy to achieve this target is carbon tax. When an enterprise is subject to a carbon tax, it has to pay this extra fee for the long-term if it does not upgrade its production technology. It needs to pay a certain upgrade fee in the short-term if it chooses to upgrade its plant. Thus, it has been an important problem for enterprises seeking to balance the trade-off between the ‘long-term tax fee’ and the ‘short-term upgrade fee’. This paper explores how to optimise an enterprise’s production technology upgrade strategy based on existing low-carbon technologies, to minimise the total upgrade cost subject to an expected total cost per product. An integer programming model is proposed to formulate the problem, and a ‘multi-agent system – genetic algorithm’ method is presented for its solution. The model is applied to a numerical example and the results indicate that the proposed method is feasible. The impacts of carbon tax and enterprise’s expected cost on its technology upgrade strategy are further discussed.